2018
DOI: 10.15381/anales.v78i4.14259
|View full text |Cite
|
Sign up to set email alerts
|

Depresión y factores asociados en la población peruana adulta mayor según la ENDES 2014-2015

Abstract: Objetivos: Estimar la prevalencia y los factores asociados a la depresión en la población peruana adulta mayor según los resultados de la Encuesta Demográfica y de Salud Familiar (ENDES) 2014-2015. Diseño: Estudio observacional, transversal y analítico. Institucion: UNMSM. Participantes: Adultos mayores. Intervenciones: Muestra probabilística de 11 411 adultos mayores que respondieron a la ENDES 2014-2015. Principales Medidas de Resultados: Prevalencias, promedios, desviaciones estándar y cálculos de OR con un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
28

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 12 publications
1
10
1
28
Order By: Relevance
“…Contrary to previous evidence in Peru [ 27 , 28 ], we found that the younger population was more prone to having depressive symptoms. However, similar results have been found in large samples in the US [ 29 ] and the UK [ 30 ] during the pandemic, where young adults showed a higher prevalence of severe psychological distress compared to older groups [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to previous evidence in Peru [ 27 , 28 ], we found that the younger population was more prone to having depressive symptoms. However, similar results have been found in large samples in the US [ 29 ] and the UK [ 30 ] during the pandemic, where young adults showed a higher prevalence of severe psychological distress compared to older groups [ 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Con respecto a la instrucción educativa y la convivencia los resultados de esta investigación concuerdan con los hallazgos de Martina 17 , quien demuestra que la población analfabeta tiene mayor frecuencia de depresión (p<0,001), igual que la población que vive sola, también se evidencia similitud con los resultados de la investigación realizada en China por Nianquan Sol 18 , quien concluyó que vivir solo y tener un nivel educativo bajo son quienes en su mayoría presentan síntomas depresivos. En esta investigación en cuanto a la ocupación se encontró significancia estadística al asociarlo con la depresión, sin embargo, estos resultados no coinciden con los encontrados por Tartaglini, quien no encontró asociación entre estas 2 variables (p 0,673).…”
Section: Discussionunclassified
“…The explanatory variables of the study were the self-reporting of diabetes mellitus (yes, no) that was evaluated with the question: "Have you ever been diagnosed with diabetes or "high blood sugar" by a doctor in your life? "; the presence of high blood pressure (yes, no) when the mean systolic blood pressure was ≥140 mmHg and/or mean diastolic blood pressure was ≥ 90 mmHg [18] or having a prior diagnosis of hypertension; the presence of depressive symptoms evaluated with the Patient Health Questionnaire (PHQ-9, yes, no) considering a PHQ-9 score ≥10 as yes [19,20]; the presence of the following combinations: diabetes and hypertension (yes, no), diabetes and depression (yes, no), hypertension and depression (yes, no); and, the presence of multimorbidity (yes, no) considered as yes in the presence of two or more of the previous diseases.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%